Non-coding RNAs participate in interactions between senescence and gastrointestinal cancers - Liu, Zhao-Zhe; Ji, Fa-He; Piao, Ying (Frontiers in Genetics, 2025)
Relationships between cellular senescence and gastrointestinal cancers have gained prominence in recent years. The currently accepted theory suggests that cellular senescence and cancer occurrence exhibit “double-edged sword” effects. Cellular senescence is related to cancer via four “meta-hallmarks” i.e., genomic instability, epigenetic alterations, chronic inflammation, and dysbiosis, along with two “antagonistic hallmarks” i.e., telomere attrition and stem cell exhaustion. These relationships are characterized by both agonistic and antagonistic elements, but the existence of an intricate dynamic balance remains unknown. Non-coding RNAs (ncRNAs) have vital roles in post-transcriptional regulation, but how they participate in agonistic and antagonistic relationships between cellular senescence and gastrointestinal cancers remains to be fully investigated. In this article, we systematically review how ncRNAs (including microRNAs (miRNAs), long ncRNAs (lncRNAs), and circularRNAs (circRNAs)) participate in interactions between cellular senescence and gastrointestinal cancers. Our aim is to elucidate a triangular relationship between “ncRNAs–senescence–gastrointestinal cancers” which considered these three elements as an equal important standing. We are keen to identify prognostic or therapeutic targets for gastrointestinal cancers from, i.e., aging-related ncRNAs, or discover novel strategies to treat and manage in the elderly. We seek to clarify complex relationships where ncRNAs participate in “senescence–gastrointestinal cancers” interactions.